STRATEGI PENGENDALIAN RISIKO PEMBIAYAAN MURABAHAH DI PERBANKAN SYARIAH - Juliana Putri; Auzia Amzar (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2018)
Murabahah financing is one of the largest sources of Islamic bank income, but at the same time is the largest source of risk for business operations, namely the emergence of troubled murabahah financing, because with the existence of troubled murabahah financing not only decreases income for Islamic banks but also affects the smooth payment activities in Islamic banks and will ultimately harm the financing customers. Therefore, risk management is needed to identify, measure, monitor and control risks in accordance with Islamic banking business activities. These steps are carried out in order to mitigate risk by considering compliance with Sharia Principles. This research is field research. The research method used in this research is descriptive qualitative method, which describes and illustrates the risk control strategies of murabahah financing at PT. Bank Aceh Syariah Samudera of Lhokseumawe. Data collection techniques carried out were interviews through speakers from the PT. Bank Aceh Syariah Samudera of Lhokseumawe. Murabahah financing risk control strategies carried out by PT. Bank Aceh Syariah Samudera of Lhokseumawe through three stages, namely the planning stage, the implementation phase and the control phase. Keywords: Strategy, Intellectual Control, Risk, Financing Murabaha, Islamic Banking.